A rare case with synchronous gastric gastrointestinal stromal tumor, pancreatic neuroendocrine tumor, and uterine leiomyoma. Issue 1 (December 2016) - Arabadzhieva, Elena; Yonkov, Atanas; Bonev, Sasho; Bulanov, Dimitar; Taneva, Ivanka; Vlahova, Alexandrina; Dikov, Tihomir; Dimitrova, Violeta
Abstract Background Although gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract, they comprise less than 1% of all gastrointestinal tumors. Neuroendocrine tumors (NET) of the gastro-enteropancreatic system are also rare, representing about 2% of all gastrointestinal neoplasms. Pancreatic localization of NET is extremely uncommon—these tumors are only 1–5% of all pancreatic cancers. Case presentation We describe an unusual case with triple tumor localization—a gastric tumor, a formation in the pancreas, which involves the retroperitoneal space, and a uterine leiomyoma. The exact diagnosis was confirmed with immunohistochemical study after surgical treatment of the patient. Distal pancreatic resection, splenectomy, partial gastrectomy, omentectomy, and hysterectomy were performed. The histological examination proved an epithelioid type of gastric GIST. Immunostaining showed focal positive expression of c-kit and no mitotic figures per 50 HPF. Histology of the pancreatic and retroperitoneal formation proved a well-differentiated NET with origin from the islets of Langerhans. The immunohistochemical study demonstrated co-expression of chromogranin A and synaptophysin. Conclusions This is the fourth case published so far of a patient with synchronous pancreatic NET and gastric GIST. The main objective of the study is to present a unique case because we have not found any reports for coexistence of the described three types of neoplasm, as in our patient, and we hope that it will be valuable in the future investigations about the genesis, diagnosis, and treatment of these types of tumors.